VD_FINDINFO HC / 2018 / 556 vom 18. Juni 2018 - VD Tribunal cantonal (2018)
CESSION DE CRÉANCECO, CESSION DE CRÉANCELP, REMISE CONVENTIONNELLE DE DETTE, SOLIDARITÉ, QUITTANCE, DÉCISION D'IRRECEVABILITÉ | 166 CC, 115 CO, 143 CO, 147 al. 2 CO, 403 CO, 88 CO, 83 al. 1 CPC (CH)